Efeitos in vitro e in vivo do extrato de glândulas salivares de fêmeas de carrapatos Rhipicephalus sanguineus com 2 dias de alimentação sobre modelos tumorais - Rocha, Fabiana Alonso [UNESP] (2014)
In this study, tests were conducted to demonstrate the antitumor potential of salivary gland extract of female ticks Rhipicephalus sanguineus 2 (EGS2) days of feeding on the DH82 cell lines HL-60 and (in vitro), as well as the effects of two different concentrations (0,2 and 0,04μg/uL) extracts (one or two injections) obtained from the same glands of the same species at the same time of tick feeding on morphophysiology muscle of hind legs of female Wistar rats inoculated with Walker 256 tumor cells (in vivo). In vitro, tumor cells were exposed to concentrations of the extract for 24 hours and then forwarded to the quantitative assessments (analysis parameters and viability percentage of total cells) and morphology (analysis under conventional light microscopy: hematoxylin and eosin and under confocal microscopy: marking cytoskeletal / core check cell viability, as well as the detection of the activity of caspases 3 and 7). The quantitative results show that the extract EGS2 adversely affects both the viability as the proliferation of tumor cells, and the concentration of 0,2 reduced the viability of DH82 and 0,5 reduced the proliferation of these. For HL-60 concentrations of 0,2 and 0,5 reduced the viability still being the concentration of 0,5 was most effective in this process. Morphological data showed that both DH82 (exposure to 0,2 mg / mL of EGS2) and HL-60 (exposure to 0,2 to 0,5 mg / mL of EGS2) had impaired viability, or in such concentrations there was death of EGS2 cell, which occurred earlier in DH82 (presence of large blocks containing cell debris). Moreover, it was detected cytoplasmic and nuclear changes resulting from exposure to the extracts, which were: a) disruption of the cytoskeleton (actin and tubulin), b) condensation of chromatin and concentration in blocks or distributed throughout the core or only on its periphery (chromatin marginalization), pyknosis, training blebbs and nuclear fragmentation, c) activity of...